Loudness and Intelligibility of Irrelevant Background Speech Differentially Hinder Children's Short Story Reading. Issue 1 (20th October 2020) - Guerra, Giada; Tijms, Jurgen; Vaessen, Anniek; Tierney, Adam; Dick, Frederic; Bonte, Milene
Abstract : Reading skills are usually assessed in silent conditions, but children often experience noisy educational settings. Effects of auditory distraction on children's reading skills remain relatively unexplored. The present study investigates the influence of two features of background speech—intelligibility and loudness—on children's reading speed and comprehension. Sixty‐three 8‐to‐10‐year‐old elementary school children performed a reading task in the context of single‐talker background speech. Background speech was either intelligible or unintelligible and presented at low (45–50 dB SPL) or moderate (65–72 dB SPL) sound intensity (here termed "loudness"). Results showed a differential effect of intelligibility and loudness, respectively affecting children's comprehension and reading speed. In addition, the intelligibility effect was larger in children with lower interference control, as assessed with an auditory Stroop task. Our findings provide evidence for the influence of different properties of background speech on children's text reading with implications for reading in everyday classroom environments. Lay Summary: Children often read in noisy environments, but we know little about how background chatter might affect their reading. Here, we found that 8–10‐year‐old children read stories more slowly with louder background speech. The children also understood less about a story if the background voice was speaking in their own language—especially those who, in a different task, were less able to ignore irrelevant but attention‐grabbing information. This suggests background speech differentially affects beginning readers. Abstract : Lay abstract: Children often read in noisy environments, but we know little about how background chatter might affect their reading. Here, we found that 8‐10‐year‐old children read stories more slowly with louder background speech. The children also understood less about a story if the background voice was speaking in their own language ‐ especially those who, in a different task, were less able to ignore irrelevant but attention‐grabbing information. This suggests background speech differentially affects beginning readers.